Celastrol reduces cisplatin-induced nephrotoxicity by downregulating SNORD3A level in kidney organoids derived from human iPSCs - Chongayng Shen; Qizheng Wang; Xun Ye; Yi Zhou; Huayang Xing; Chengjie Pan; Heying Li; Chunjie Wu; Mingliang You (Frontiers in Pharmacology)
BackgroundCelastrol, an active ingredient derived from Tripterygium wilfordii Hook F, has shown therapeutic potential for various kidney renal diseases. The kidney protective activity of celastrol is mainly exerted through anti-inflammatory, and antioxidant effects. However, celastrol causes dose-dependent kidney toxicity, which results in increased risks of mortality among patients. This study aimed to develop a kidney organoid-based prediction system to assess the safety and efficacy of celastrol in reducing cisplatin-induced nephrotoxicity.MethodsWe investigated the ability of celastrol to reduce cisplatin-induced nephrotoxicity using kidney organoids. Kidney organoids were cultured and characterized, exhibiting renal tubular and glomerular structures and expressing specific kidney markers such as NPHS1, CD31, LTL, and SLC12A1. Data were obtained from in vitro experiments in which kidney organoids were exposed to therapeutically relevant concentrations or a toxic dosing profile of cisplatin and celastrol, to assess their impact on cell viability using flow cytometry and Acridine Orange/Propidium Iodide (AO/PI) staining. In addition, RNA-seq analyses were performed to determine the mechanisms of celastrol function in the kidney.ResultsKidney organoids exposed to 50 µM cisplatin showed significantly increased cell death (only 0.37% cells with normal cell structure), whereas celastrol under 5 µM (56% cells with normal cell structure) showed significantly less nephrotoxicity than cisplatin. The protective effects of celastrol against cisplatin-induced nephrotoxicity were further investigated by treating the organoids with both compounds. The results demonstrated that 2 µM celastrol reduced cisplatin-induced nephrotoxicity by downregulating SNORD3A and HIST1H3A gene levels.ConclusionThis study highlights the potential of celastrol as a protective compound against cisplatin-induced kidney damage and emphasizes the importance of using advanced models, such as iPSC-derived kidney organoids, to predict therapeutic effect and nephrotoxic concentrations of novel drugs.